2020
DOI: 10.1101/lm.051243.119
|View full text |Cite
|
Sign up to set email alerts
|

Systems consolidation impairs behavioral flexibility

Abstract: Behavioral flexibility is important in a changing environment. Previous research suggests that systems consolidation, a longterm poststorage process that alters memory traces, may reduce behavioral flexibility. However, exactly how systems consolidation affects flexibility is unknown. Here, we tested how systems consolidation affects: (1) flexibility in response to value changes and (2) flexibility in response to changes in the optimal sequence of actions. Mice were trained to obtain food rewards in a Y-maze b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Several studies point to hippocampal maturation as a major factor in guiding the onset of fear memory persistence, likely by enabling the long-term retrieval of infant memories. Furthermore, our data show that a correlate of remote memory retrieval, activation of the prefrontal cortex (Takehara et al 2003;Frankland et al 2004a;Frankland and Bontempi 2005;Vetere et al 2011;Wheeler et al 2013;Kitamura et al 2017;DeNardo et al 2019;Grella et al 2020;Pan et al 2020;Sathiyakumar et al 2020), is absent for infant memories. Interestingly, Guskjolen et al (2018) found that adult retrieval of P17 memories through optogenetic manipulation of hippocampal neuronal ensembles reinstated patterns of neuronal activity in brain regions such as the entorhinal cortex, but not PL.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Several studies point to hippocampal maturation as a major factor in guiding the onset of fear memory persistence, likely by enabling the long-term retrieval of infant memories. Furthermore, our data show that a correlate of remote memory retrieval, activation of the prefrontal cortex (Takehara et al 2003;Frankland et al 2004a;Frankland and Bontempi 2005;Vetere et al 2011;Wheeler et al 2013;Kitamura et al 2017;DeNardo et al 2019;Grella et al 2020;Pan et al 2020;Sathiyakumar et al 2020), is absent for infant memories. Interestingly, Guskjolen et al (2018) found that adult retrieval of P17 memories through optogenetic manipulation of hippocampal neuronal ensembles reinstated patterns of neuronal activity in brain regions such as the entorhinal cortex, but not PL.…”
Section: Discussionmentioning
confidence: 61%
“…While studies have implicated developmental changes in the hippocampus in infantile forgetting ( Akers et al 2014 ; Guskjolen et al 2018 ; Travaglia et al 2018 ), much less is known about the contribution of other brain areas involved in remote memory, such as the prefrontal cortex ( Takehara et al 2003 ; Frankland et al 2004a ; Frankland and Bontempi 2005 ; Vetere et al 2011 ; Wheeler et al 2013 ; Kitamura et al 2017 ; DeNardo et al 2019 ; Grella et al 2020 ; Pan et al 2020 ; Sathiyakumar et al 2020 ), in this process. In adult rodents, recruitment of neuronal activity in the prelimbic cortex (PL) has been shown to occur following remote, but not recent, fear memory retrieval (Frankland et al 2004a; Wheeler et al 2013 ; DeNardo et al 2019 ; Grella et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations